Roundabouts : an informational guide. - Rodegerdts, Lee A. 1970-; Robinson, Bruce W. (Transportation Research Board, 2010)
TRB's National Cooperative Highway Research Program (NCHRP) Report 672: Roundabouts: An Informational Guide - Second Edition explores the planning, design, construction, maintenance, and operation of roundabouts. The report also addresses issues that may be useful in helping to explain the trade-offs associated with roundabouts. This report updates the U.S. Federal Highway Administration's Roundabouts: An Informational Guide, based on experience gained in the United States since that guide was published in 2000.
Revised edition of: Roundabouts : an informational guide / [principal investigator, Bruce W. Robinson]; FHWA project manager, Joe Bared. 2000.
"National Cooperative Highway Research Program in cooperation with U.S. Department of Transportation, Federal Highway Administration"--Cover
Keywords: Traffic circles -- United States -- Design and construction.; Roads -- United States -- Interchanges and intersections -- Design and construction.; elektronické knihy; electronic books